Perancangan Ulang User Interface Website Galaxyplb Berbasis User Experience dengan Design Thinking - Patricia, Vera; Sihotang, Fransiska Prihatini (MDP Student Conference, 2025)
Effective user interface design is a key factor in enhancing user experience on digital platforms. Galaxyplb is a digital platform used by CV Galaxy Autoparts to support operational activities. However, user experience analysis reveals issues such as low text readability, confusing layouts, and lack of system feedback. This study aims to redesign the user interface using the user-centered Design Thinking method. The process follows the Empathize, Define, Ideate, Prototype, and Test stages, utilizing UEQ for user experience evaluation and Figma for prototyping. Initial UEQ evaluation indicates negative ratings across most UX aspects. The redesigned interface is tested again with UEQ, showing significant improvements in all UX aspects. The results confirm that the new design better meets user needs and enhances satisfaction.